A South African public- private partership HIV treatment model: viability and success factors - Ingumbor J; Pascoe S; Rajap S; et al (My University, 2014)
Introduction:The increasing number of people requiring HIV treatment in South Africa calls for efficient use of its human resources for health in order to ensure optimum treatment coverage and outcomes. This paper describes an innovative public-private partnership model which uses private sector doctors to treat public sector patients and ascertains the model's ability to maintain treatment outcomes over time. Methods: The study used a retrospective design based on the electronic records of patients who were down-referred from government hospitals to selected private general medical practitioners (GPs) between November 2005 and October 2012. In total, 2535 unique patient records from 40 GPs were reviewed. The survival functions for mortality and attrition were calculated. Cumulative incidence of mortality for different time cohorts (defined by year of treatment initiation) was also established. Results:The median number of patients per GP was 143 (IQR: 66-246). At the time of down-referral to private GPs, 13.8% of the patients had CD4 count <200 cell/mm3, this proportion reduced to 6.6% at 12 months and 4.1 % at 48 months. Similarly, 88.4% of the patients had suppressed viral load (defined as HIV-1 RNA <400 copies/ml) at 48 months. The patients' probability of survival at 12 and 48 months was 99.0% (95% Cl: 98.4%-99.3%) and 89.0% (95% Cl: 87.1%-90.0%) respectively. Patient retention at 48 months remained high at 94.3% (95% Cl: 93.0%-95.7%). Conclusions:T\ne study findings demonstrate the ability of the GPs to effectively maintain patient treatment outcomes and potentially contribute to HIV treatment scale-up with the relevant support mechanism. The model demonstrates how an assisted private sector based programme can be effectively and efficiently used to either target specific health concerns, key populations or serve as a stop-gap measure to meet urgent health needs.
PK
Keywords: HIV Infections/mortality; HIV Infections/therapy; South Africa/epidemiology